1999
DOI: 10.1029/1998gl900244
|View full text |Cite
|
Sign up to set email alerts
|

Observation of short‐term variation of Jupiter's synchrotron radiation

Abstract: Abstract.Detailed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 16 publications
0
49
0
2
Order By: Relevance
“…The observation of changes in the emission from Jupiter's electron belt has been reported since the early 1970s (e.g., Gérard 1970; Klein et al 1972Klein et al , 1989. Correlations with solar wind on timescales of months to years (e.g., Bolton et al 1989;Galopeau & Gérard 2001;Santos-Costa et al 2008) and solar radio flux on timescales of days to a week (e.g., Miyoshi et al 1999;Tsuchiya et al 2011;Kita et al 2013) have been confirmed since the 1990s. However, the response of the electron belt to the solar wind on short timescales has never been considered until the present work.…”
Section: Discussionmentioning
confidence: 84%
“…The observation of changes in the emission from Jupiter's electron belt has been reported since the early 1970s (e.g., Gérard 1970; Klein et al 1972Klein et al , 1989. Correlations with solar wind on timescales of months to years (e.g., Bolton et al 1989;Galopeau & Gérard 2001;Santos-Costa et al 2008) and solar radio flux on timescales of days to a week (e.g., Miyoshi et al 1999;Tsuchiya et al 2011;Kita et al 2013) have been confirmed since the 1990s. However, the response of the electron belt to the solar wind on short timescales has never been considered until the present work.…”
Section: Discussionmentioning
confidence: 84%
“…Continuous observations showed that JSR significantly increased 1 to 2 days after the Shoemaker‐Levy 9 comets collided with Jupiter in 1994. Many astronomical research groups have reported short‐term variations in JSR since these events [ Bhardwaj et al , ; Bolton et al , ; Imai , ; Klein et al , ; Misawa and Morioka , ; Miyoshi et al , ; Nomura , ; Santos‐Costa et al , ; Tsuchiya et al , , ]. These variations indicate that the electron density and/or energy is affected by physical processes such as acceleration, transport, and loss of relativistic electrons.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, single‐dish observations have supported the B‐M scenario. Miyoshi et al [] reported that a short‐term variation event at 2.3 GHz was well correlated with the solar F10.7, which is known to be a good proxy for the solar UV/EUV flux index. Tsuchiya et al [] demonstrated that the total flux variation in JSR at 325 MHz is positively correlated with the solar UV/EUV index and they used a radial diffusion model to examine the B‐M scenario.…”
Section: Introductionmentioning
confidence: 99%
“…Both short-and long-term variations have been reported to exist in Jupiter's radiation belts. Correlations found with solar wind variations (Bolton et al 1989) and solar F10.7 flux enhancements (Miyoshi et al 1999) have been proposed to be related to the long-and short-term variations, accordingly. Finally, wave-particle interactions also constitute both source and loss acceleration mechanisms in the system.…”
Section: Space Weather At the Radiation Beltsmentioning
confidence: 99%
“…One such example is the radiation detector of the Mars Radiation Environment Experiment (MARIE) on-board Mars Odyssey (Andersen 2006), which was presumed to have failed due to damage from the unusually intense SEP events of OctoberNovember 2003. Another example involved the Nozomi spacecraft, which suffered disruptions to its communication system due to a solar flare occurring in April 2002 (Miyasaka et al 2003). Another major space weather event resulted in an increase in background radiation that made it difficult for the Analyser of Space Plasmas and Energetic Atoms 3 (ASPERA-3) instrument on-board Mars Express (MEX) to evaluate ion escape fluxes at Mars ).…”
Section: Motivation For Researchmentioning
confidence: 99%